White Papers for Dummies - Graham, Gordon (Hoboken, New Jersey John Wiley & Sons, Inc., 2013)
A fast and easy way to write winning white papers! Whether you're a marketing manager seeking to use white papers to promote your business, or a copywriter keen to break into this well-paying field, White Papers For Dummies gives you a wealth of practical, hands-on advice from one of the world's leading experts in the field. The fact-based documents known as white papers have been called the "king of content." No other B2B marketing piece can do more to generate leads, nurture prospects, and build mindshare
Includes Index and Illustrations.
Keywords: Business writing